2002
DOI: 10.1097/00002060-200202000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Carpal Tunnel Syndrome with Nerve and Tendon Gliding Exercises

Abstract: Although the results in group 2 were better than group 1, the difference was not statistically significant. Further investigations are required to establish the role of nerve and tendon gliding exercises in the treatment of carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
1
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 24 publications
5
143
1
9
Order By: Relevance
“…Last, a small randomised study did not evidence any significant difference between the association between nerve and tendon gliding exercises (aimed at restoring the maximum excursion of the median nerve and of the carpal tunnel tendons) and the use of wrist splints as compared to splinting alone in terms of symptoms or function improvement after 8 weeks from the end of treatment [34].…”
Section: Hand and Wrist Splintingmentioning
confidence: 93%
“…Last, a small randomised study did not evidence any significant difference between the association between nerve and tendon gliding exercises (aimed at restoring the maximum excursion of the median nerve and of the carpal tunnel tendons) and the use of wrist splints as compared to splinting alone in terms of symptoms or function improvement after 8 weeks from the end of treatment [34].…”
Section: Hand and Wrist Splintingmentioning
confidence: 93%
“…One review showed good results for splinting, ultrasound, nerve gliding exercises, carpal bone mobilization, magnetic therapy, and yoga for people with carpal tunnel syndrome (8). Combined therapy may be more effective than the use of any single modality (8)(9)(10). However, a recent guideline produced by the American Academy of Orthopedic Surgeons assigned lower grades of evidence to most of these treatments (11).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several authors have stated that the exercises utilized were chosen solely on those used in previous studies. 1,3,4,32,41 The use and description of neural mo-T T STUDY DESIGN: Controlled laboratory study using a single-group, within-subjects comparison.…”
mentioning
confidence: 99%